Scientific and Methodological Support of Accounting at the Enterprise (Economics and region, 2018)
The article deals with the issues of automation of the personnel accounting and accounting of calculations of the enterprise with suppliers and contractors, the automation of development of a software product which serves to save both financial resources and labor resources of the enterprise, is described. The authors also characterized the automation of internal accounting. The peculiarities of theoretical and practical aspects of the application of the computer program in the organization of accounting at the enterprise are also revealed. Use of the software product developed by us in accounting should lead to increase of efficiency of activity of the enterprise. The developed software will provide maximum efficiency of enterprise management in general and accounting systems in particular. An alternative to a software product is its adaptation to the specific conditions of the enterprise. The stages of accounting unification are summarized in accordance with the methods of implementation of automation elements at the enterprise. The main advantages of introducing a software product at the enterprise are determined. The purpose of the article is to reveal the practical aspects of the functioning of the software product, which corresponds to the basic functional accounting requirements, has the ability to conduct accounting, analytical, controlling work, to take into account the specific features of the enterprise. The practical results obtained during the study process solve the problem of justifying the need for application software for enterprise management.
Keywords: software product; automation; accounting; managerial accounting information systems; computer programs; personnel